Patient Assessments of the Factors Facilitating and Impeding User Involvement During the First Phase of Substance Abuse Treatment - Merethe Wenaas; Nina Kavita Heggen Bahl; Riina Kiik; Anne Juberg (SAGE Publishing, 2021)
User involvement in the first phase of treatment is essential for treatment satisfaction among patients with substance use disorders (SUDs). This study explores how patients perceive the first phase of specialized SUD treatment and identifies what promotes and inhibits user involvement. We used a qualitative approach, and semi-structured interviews were conducted with 14 informants admitted to a substance abuse treatment unit in central Norway. The analysis was inspired by a phenomenographical analysis approach, and 4 categories were identified as the core experiences of user involvement during the first phase of SUD treatment: (a) a new hold on life, (b) missing information, (c) the importance of a sense of community, and (d) ambivalence about the usefulness of the treatment. Overlapping elements with Aaron Antonovsky's theoretical framework of salutogenesis were used to support the main findings. The study indicates that activating personal resources (eg, the ability to envision a different life), conveying information in a matter sensitive to patients' current cognitive state, a sense of community, and therapeutic alliance are essential factors to promote user involvement in the first phase of specialized SUD treatment. Based on the findings, we suggest a salutogenesis approach to promote user involvement and provide several ways to employ this approach in the crucial first phase of specialized SUD treatment.